Development of a measure of prescriber satisfaction with academic detailing: the PSAD - Andrea L Monteiro; Mary Smart; Christopher D Saffore; Todd A Lee; Sarette T Tilton; Michael A Fischer; A Simon Pickard (BioExcel Publishing Ltd, 2022)
Introduction: Academic detailing (AD) is an educational outreach strategy to provide clinicians with current evidence-based information, which has been shown to change prescribing behaviours. The overall effectiveness of AD interventions is associated with prescriber satisfaction; however, most approaches use single items or nonvalidated measures. This study aims to develop and validate an instrument to assess prescriber satisfaction with AD interventions. Methods: A group of candidate items was generated and refined based on constructs identified through a literature review and in consultation with an expert panel. The initial instrument was piloted with 183 primary care providers who participated in an AD intervention on opioid-related pain management. To support the validity and reliability of the measure, psychometric properties were examined. Results: Ten candidate items were developed based on the following themes: acceptability, feasibility of implementation, usefulness, perception of efficacy, overall satisfaction, willingness to repeat and willingness to change. One item related to willingness to change did not contribute to assessing an individual's ability and lowered the measure's internal consistency and was therefore dropped. Conclusion: Results supported the validity and reliability of a refined 9-item measure of Provider Satisfaction with Academic Detailing (the PSAD). This measure should be considered for broad use across educational outreach programmes as a standardized measure to assess provider satisfaction and provide continuous quality improvement.